2022
DOI: 10.3390/ijms23169014
|View full text |Cite
|
Sign up to set email alerts
|

Combination RSL3 Treatment Sensitizes Ferroptosis- and EGFR-Inhibition-Resistant HNSCCs to Cetuximab

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are a type of cancer originating in the mucosal epithelium of the mouth, pharynx, and larynx, the sixth most common cancer in the world. However, there is no effective treatment for HNSCCs. More than 90% of HNSCCs overexpress epidermal growth factor receptors (EGFRs). Although small molecule inhibitors and monoclonal antibodies have been developed to target EGFRs, few EGFR-targeted therapeutics are approved for clinical use. Ferroptosis is a new kind of programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…3 F). Because nuclear receptor coactivator 4 (NCOA4), SLC3A2, GPX4, ACSL3, and FTH1 were previously established to control ferroptosis in tumor cells [ [40] , [41] , [42] , [43] ], we focused on the role of IGF2BP3 in ferroptosis in the current study.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…3 F). Because nuclear receptor coactivator 4 (NCOA4), SLC3A2, GPX4, ACSL3, and FTH1 were previously established to control ferroptosis in tumor cells [ [40] , [41] , [42] , [43] ], we focused on the role of IGF2BP3 in ferroptosis in the current study.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…KEGG analysis revealed that the HIF-1 signaling pathway and NOD-like receptor signaling pathway To further clarify the mechanisms underlying ferroptosis activation in IRI, a PPI network of DEFRGs was constructed, and several hub genes were identified, of which HIF1A, EGFR, HMOX1, and ATF3 were validated experimentally in an in vitro A/R model. Previous studies showed that these critical genes participate in the regulation of ferroptosis (46)(47)(48)(49). Furthermore, the HIF1A/PTGS2 pathway aggravates ferroptosis and mediates myocardial injury and inflammation after coronary microembolization (50).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was shown that QSOX1 inhibited EGFR signal activation by enhancing ubiquitination-mediated degradation of EGFR, leading to sorafenib induced ferroptosis of hepatocellular carcinoma cells [ 67 ]. The ferroptosis inducer RSL3 showed a synthetic role with EGFR inhibitor, Cetuximab, to exacerbate the ferroptosis of nasopharyngeal carcinoma cells [ 68 ]. However, no studies have investigated the role of EGFR in chondrocytes ferroptosis.…”
Section: Discussionmentioning
confidence: 99%